The impact of lean production and flexible manufacturing strategies on financial performance of manufacturing companies in Nigeria - Wan Norhayate, Wan Daud; Okocha Onyeka, Linus (Penerbit Universiti Sultan Zainal Abidin, 2020)
This research aims to investigate the impact of lean production strategy (LPS) and flexible manufacturing strategy (FMS) on financial performance (FP) in the Nigerian manufacturing sector (NMS). A quantitative research approach was applied, and a simple random sampling technique was chosen to identify the samples for this study. For this reason, data were collected from 101 manufacturing companies in Nigeria and a statistical tool; Statistical Package for Social Science (SPSS) version 26 was used to analyze the data. The result shows a significant relationship among the factors examined. Among the factors, the independent variable (LPS) had shown the most decisive impact compared to (FMS) on the dependent variable (FP) the study suggested. Findings from the study contribute and support Porter’s generic theory on existing literature, and practically to the Nigerian manufacturing companies by providing insights into this research area.